Avaliação da qualidade de cursos de graduação na modalidade educação a distância sob a perspectiva dos discentes - Rodrigues, Elana Flávia de Sousa (2018)
E-learning is increasingly present in the scenario of Brazilian higher education, fostering the provision of higher education courses over the years. It is in this context that this research investigated the e-learning, considering that the expansionist character of this modality should not be prioritized to the detriment of the quality of the offered education. In this sense, it was sought to understand the development of the e-learning, tracing a historical course in the world and national scope, also reflecting on the construction of the image of e-learning in the Brazilian territory from the legal documents that instituted it as a teaching modality. The relevance of maintaining the quality of e-learning was discussed, referring to the evaluation of teaching and learning as one of the alternatives to guarantee the quality of this modality. This research aimed to evaluate the quality of the undergraduate courses of the Federal University of Ceará under the perspective of the students. For this, a field research was carried out, with descriptive character and quantitative nature, using the case study as a method, applying a structured questionnaire, which was a reapplication of the QEOn, Instrument of evaluation of Quality of Teaching Online, developed by Silva et al (2017). The results showed that the undergraduate courses in the e-learning of the UFC obtained a satisfactory evaluation in the five dimensions proposed in this research, presenting a mean of positive responses of 73.73% for the dimension "Online Tutor Profile", 80.15% for "Relation Tutor Attendance / Cursist ", 83.85% for" Online Tutor Interaction", 78.29% for" Assessment Processes "and 85.84% for" Learning ". From these results, it was verified that e-learning courses in the UFC have a considerable degree of quality in the view of the students.